Shuffling the deck with CTLA-4 therapy: Deep sequencing of rearranged TCRB genes demonstrates T cell repertoire remodeling in cancer patients. (3rd April 2018) - Cha, Edward; Fong, Lawrence
ABSTRACT: CTLA-4 inhibition produces durable T cell–driven antitumor responses, but understanding which patients achieve a long-term benefit remains unclear. Deep sequencing of rearranged T cell receptor β (TCRβ) genes can monitor the effects of CTLA-4 inhibition and potentially identify patients with long-term survival.